2009
DOI: 10.1039/b915265b
|View full text |Cite
|
Sign up to set email alerts
|

The pyridinone-methide elimination

Abstract: The quinone-methide elimination is a common, efficient methodology used in linkers designed to undergo self-fragmentation. Here, for the first time, we demonstrate this elimination in a pyridine ring system. Under physiological conditions, a compound constructed of a pyridine core, a reporter, and an enzymatic trigger underwent significantly faster 1,4-elimination than its parent compound with a benzene core. In addition, an AB(2) self-immolative dendron based on a pyridine core released its two reporter units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 18 publications
0
28
0
3
Order By: Relevance
“…150 kJ mol À1 ), [123] so should be favorable to build fast self-immolative spacers.This was observed in as pacer containing the pyridinic core (formula 31;F igure 6). [108] After enzymatic activation, its self-immolation was complete after 30 min, compared to more than 4hfor the benzenic analogue. [108] In contrast, other results (see Table 2S) relying on photochemical activation and detailed kinetic analysis demonstrated that the pyridine ring decreases the rate of disassembly relative to the benzene core (see formulas 34 and 37 relatively to others) and that the position of its nitrogen atom is significant (see formulas 31 and 32).…”
Section: Aromatic Corementioning
confidence: 98%
See 1 more Smart Citation
“…150 kJ mol À1 ), [123] so should be favorable to build fast self-immolative spacers.This was observed in as pacer containing the pyridinic core (formula 31;F igure 6). [108] After enzymatic activation, its self-immolation was complete after 30 min, compared to more than 4hfor the benzenic analogue. [108] In contrast, other results (see Table 2S) relying on photochemical activation and detailed kinetic analysis demonstrated that the pyridine ring decreases the rate of disassembly relative to the benzene core (see formulas 34 and 37 relatively to others) and that the position of its nitrogen atom is significant (see formulas 31 and 32).…”
Section: Aromatic Corementioning
confidence: 98%
“…[108] After enzymatic activation, its self-immolation was complete after 30 min, compared to more than 4hfor the benzenic analogue. [108] In contrast, other results (see Table 2S) relying on photochemical activation and detailed kinetic analysis demonstrated that the pyridine ring decreases the rate of disassembly relative to the benzene core (see formulas 34 and 37 relatively to others) and that the position of its nitrogen atom is significant (see formulas 31 and 32). Moreover,i th as even been shown that the introduction of two nitrogen atoms in the aromatic core (pyrimidines;f ormulas 33 and 35)p revents release of the leaving group under acidic conditions.T hus,m ore than the drop of the resonance energy,i ts eems that disassembly kinetics of the heterocyclic self-immolative spacer is controlled by the electron density at the benzylic carbon atom bearing the leaving group.This electron density is lowered by the presence of nitrogen atoms exerting electron-withdrawing effects.…”
Section: Aromatic Corementioning
confidence: 98%
“…We have shown that the pyridinone-methide elimination can take place in a pyridine-based linker in a manner analogous to that from a benzene-based system. 33 Dendron 8 was composed with two reporter units attached to a pyridine core and phenylacetamide group as a triggering substrate (Figure 9). The dendron releases phenolate 8a upon reaction with the enzyme PGA.…”
Section: ■ the Pyridinone-methide Eliminationmentioning
confidence: 99%
“…Apart from PABA, some analogs, such as ortho ‐aminobenzyl alcohol (OABA), (5‐aminopyridin‐2‐yl)methanol, and (3‐aminopyridin‐2‐yl)methanol, are also acceptable self‐immolative linkers. Because of the lightweight structural variation among these linkers, the spontaneous decomposition rate are varied: (5‐aminopyridin‐2‐yl)methanol > PABA, (3‐aminopyridin‐2‐yl)methanol > OABA, and PABA > OABA . There are other linkers that combine the function of PABA and OABA, the self‐immolative dendrimers .…”
Section: Activable Probesmentioning
confidence: 99%
“…Because of the lightweight structural variation among these linkers, the spontaneous decomposition rate are varied: (5-aminopyridin-2-yl)methanol > PABA, (3-aminopyridin-2-yl)methanol > OABA, and PABA > OABA. 54,57 There are other linkers that combine the function of PABA and OABA, the self-immolative dendrimers. 65,66 This type of probe can usually connect one substrate with two or three reporters.…”
Section: B Substrate-self-immolative Linker-fluorophore Probesmentioning
confidence: 99%